Prediction of the Archaeal Exosome and Its Connections with the Proteasome and the Translation and Transcription Machineries by a Comparative-Genomic Approach - Koonin, Eugene V.; Wolf, Yuri I.; Aravind, L. (Genome Research, 2001)
By comparing the gene order in the completely sequenced archaeal genomes complemented by sequence profile analysis, we predict the existence and protein composition of the archaeal counterpart of the eukaryotic exosome, a complex of RNAses, RNA-binding proteins, and helicases that mediates processing and 3′->5′ degradation of a variety of RNA species. The majority of the predicted archaeal exosome subunits are encoded in what appears to be a previously undetected superoperon. In Methanobacterium thermoautotrophicum, this predicted superoperon consists of 15 genes; in the Crenarchaea, Sulfolobus solfataricus andAeropyrum pernix, one and two of the genes from the superoperon, respectively, are relocated in the genome, whereas in other Euryarchaeota, the superoperon is split into a variable number of predicted operons and solitary genes. Methanococcus jannaschiipartially retains the superoperon, but lacks the three core exosome subunits, and in Halobacterium sp., the superoperon is divided into two predicted operons, with the same three exosome subunits missing. This suggests concerted gene loss and an alteration of the structure and function of the predicted exosome in theMethanococcus and Halobacterium lineages. Additional potential components of the exosome are encoded by partially conserved predicted small operons. Along with the orthologs of eukaryotic exosome subunits, namely an RNase PH and two RNA-binding proteins, the predicted archaeal exosomal superoperon also encodes orthologs of two protein subunits of RNase P. This suggests a functional and possibly a physical interaction between RNase P and the postulated archaeal exosome, a connection that has not been reported in eukaryotes. In a pattern of apparent gene loss complementary to that seen inMethanococcus and Halobacterium, Thermoplasma acidophilum lacks the RNase P subunits. Unexpectedly, the identified exosomal superoperon, in addition to the predicted exosome components, encodes the catalytic subunits of the archaeal proteasome, two ribosomal proteins and a DNA-directed RNA polymerase subunit. These observations suggest that in archaea, a tight functional coupling exists between translation, RNA processing and degradation, (apparently mediated by the predicted exosome) and protein degradation (mediated by the proteasome), and may have implications for cross-talk between these processes in eukaryotes.